Effect of Powder to Liquid Ratio on the Push Out Bond Strength of Biodentine TM - Chalermsurakarn, Yanin; Dumrongvute, Kulanun; Sakdee, Jaruma (Khon Kaen University Dental Journal, 2022)
The objective of this study was to determine the effect of different powder-to-liquid ratio on the push out bond strength of BiodentineTM (BD). The methods used in this study were as follows: 32 single root permanent human teeth were open access with round diamond burs and prepared root canal with peeso reamer burs no.1-4, respectively. The size of the final diameter of the root canal is 1.4 mm. The prepared root canals were randomly filled with four types of material: MTA BD1:4 BD1:5 and BD1:6. The roots were cut into 3-mm thick sections and 16 samples of each group were randomized and then divided into two groups. The push-out test was performed with a Universal Testing Machine at 24 hours and 28 days after storage in PBS. The results were statistically analyzed using One-way ANOVA and Tukey's HSD test. The results of this study were as follows: at 24 hours, the highest push-out bond strength in BD1:6 that is 17.569 MPa with statistically significant differences. In contrast, at 28 days, the BD1:5 and BD1:4 groups showed a significantly higher push-out bond strength at 15.619 and 14.704 MPa than BD1:6 and MTA that are 10.169 and 10.725 MPa. In conclusion, a different powder-to-liquid ratio affected the push out bond strength of BiodentineTM, and BD1:5 and BD1:4 showed higher push-out bond strength than BD1:6 with a statistically significant difference.